Neuroanatomical and cognitive correlates of visual hallucinations in Parkinson's disease and dementia with Lewy bodies: Voxel-based morphometry and neuropsychological meta-analysis. (September 2021) - Pezzoli, Stefania; Sánchez-Valle, Raquel; Solanes, Aleix; Kempton, Matthew J.; Bandmann, Oliver; Shin, Jae Il; Cagnin, Annachiara; Goldman, Jennifer G.; Merkitch, Doug; Firbank, Michael J.; Taylor, John-Paul; Pagonabarraga, Javier; et al.
Highlights: Lewy body disease (LBD) includes dementia with Lewy bodies and Parkinson's disease. We meta-analyzed anatomical/cognitive studies of visual hallucinations (VH) in LBD. VH were associated with reduced occipital, temporal, frontal, and parietal grey matter. VH without dementia were associated with deficits in verbal immediate memory. Abstract: Visual hallucinations (VH) are common in Parkinson's disease and dementia with Lewy bodies, two forms of Lewy body disease (LBD), but the neural substrates and mechanisms involved are still unclear. We conducted meta-analyses of voxel-based morphometry (VBM) and neuropsychological studies investigating the neuroanatomical and cognitive correlates of VH in LBD. For VBM (12 studies), we used Seed-based d Mapping with Permutation of Subject Images (SDM-PSI), including statistical parametric maps for 50% of the studies. For neuropsychology (35 studies), we used MetaNSUE to consider non-statistically significant unreported effects. VH were associated with smaller grey matter volume in occipital, frontal, occipitotemporal, and parietal areas (peak Hedges' g -0.34 to -0.49). In patients with Parkinson's disease without dementia, VH were associated with lower verbal immediate memory performance (Hedges' g -0.52). Both results survived correction for multiple comparisons. Abnormalities in these brain regions might reflect dysfunctions in brain networks sustaining visuoperceptive, attention, and executive abilities, with the latter also being at the basis of poor immediate memory performance.